Life-history strategies in two subarctic lakes with polymorphic Arctic charr Salvelinus alpinus L. populations. High across lakes stability in evolution of life-history strategies - Kjær, Runar (UiT Norges arktiske universitet, 2018)
Life history strategies of polymorphic Arctic charr in two sub-arctic lakes (Tårnvatn and Skøvatn) with similar environmental- and physiochemical conditions were studied. Disparities in life history traits may reflect ecological adaptations and is suggested an important factor in the incipient speciation process. In this region several lakes have polymorphic charr, and the designation of a fish to a morph-group was based on external morphology verified through genetic differences. The trimorphic population in Tårnvatn has one littoral omnivore (LO), a small-sized profundal benthivore (PB), and a large-sized profundal piscivore (PP) morph. Skøvatn has in addition to the LO-morph, a novel profundal zooplanktivore morph (PZ). The PZ-morph closely resembles the PB-morph in terms of external morphology (cryptic coloration, large eye-size, blunt snout) and several life-history traits. Compared with their sympatric LO-morph, the PZ- and PB-morphs had an early age (4 and 5 years) and size (<100 mm and <110 mm) at sexual maturity, similar as in two other nearby lakes. The PP-morph resemble a higher age at maturity compared to the co-occurring LO-morph. Intra-lake morph comparisons revealed also distinct disparities regarding population growth parameters calculated with von Bertalanffys’ growth model. The different life-history trajectories regarding growth parameters and reproductive strategies between morph are reflected by divergent trophic niches. Thus, there are high across lakes stability in life-history traits among polymorphic Arctic charr populations occupying similar ecological niches in this region in northern Norway. Keywords: Life-history, polymorphism, parallel evolution, Arctic charr, Salvelinus alpinus